Planning Dakwah Majelis Taklim Aumin Kota Medan dalam Meningkatkan Minat Ibu-Ibu Membaca Al-Qur'an - Alya Afriannisa; Soiman (Kartika: Jurnal Studi Keislaman, 2026)
Da’wah planning is an essential element in the success of majelis taklim activities, particularly in increasing congregants’ interest in learning the Qur’an. The AUMIN Majelis Taklim (Alumni Umrah Al-Amin) in Medan City, as a forum for religious guidance for women, plays a important role in fostering awareness and love for reading the Qur’an. This study aims to examine the da’wah planning implemented by the AUMIN Majelis Taklim of Medan City in increasing women’s interest in reading the Qur’an, as well as the supporting and inhibiting factors in its implementation. This research employs a qualitative approach with a descriptive method, using data collection techniques such as observation, interviews, and documentation. The results indicate that the da’wah planning of the AUMIN Majelis Taklim in Medan City includes determining da’wah objectives, preparing materials that are aligned with the needs of the congregation, selecting persuasive and sustainable da’wah methods, and arranging flexible schedules and activities. Systematic and needs-based da’wah planning has proven effective in increasing women’s interest in reading the Qur’an. Therefore, effective da’wah planning is a key factor in optimizing the role of majelis taklim as a means of community religious development